(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Nanosized initial tin dioxide for sensors has been synthesized by sol-gel technique. Nanosized Pd/SnO2 sensor materials with average particles sizes 14–15 nm have been prepared by wet impregnation method. For the sensor material without palladium an average particle size was approximately 20 nm. Catalytic activities of the Pd/SnO2 materials in a methane oxidation reaction have been studied and their influence on formation of corresponding adsorption semiconductor sensors responses to 937 ppm of CH4 has been investigated. It was shown that the catalytic activities of the samples increase with increasing of loaded palladium content. Dependences of the sensor responses on palladium content have an extreme characters with maximum for the sensors based on the material containing 1.41 wt.% of Pd. It could be attributed to a role of an interface between palladium clusters and tin dioxide. The interface consists of defects that can chemisorb oxygen from the air. A quantity of such defects depends on the length of the interface – a longer interface consists of a larger amount of the defects. Thus the influence of the interface length on values of electrical resistances of the sensors in air should be significant. Indeed the sensor based on 1.41wt. % Pd/SnO2 material has the highest value of the electrical resistance in air owing to their longest interface. The sensors with longest interfaces can chemisorb more oxygen. As a result, rates of methane oxidation reaction on surfaces of such sensors will be higher because methane activated on the palladium clusters could be oxidized by oxygen chemisorbed on the interface. Therefore, sensors with higher values of electrical resistances should demonstrate greater sensor responses. This assumption is in agreement with experimental data. Kinetic of the methane oxidation reaction has been also investigated in excess of oxygen for the sensor material 1.41wt. % Pd/SnO2 with the highest sensor response. The first order for methane and zero order for oxygen were occurred for the reaction. A value of activation energy of the reaction is 78±4 kJ/mol that is in agreement with literature data.